2012
DOI: 10.2174/138161212802083725
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention with Phytonutrients and Microalgae Products in Chronic Inflammation and Colon Cancer

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disorder caused by deregulated immune responses in a genetically predisposed individual. This is a complex process mediated by cytokines, chemokines, adhesion molecules, cytoplasm nuclear receptors, among others. Recent data support a participation of the endoplasmic reticulum (ER) stress and mitochondrial dysfunctions in IBD. Moreover, now it is evident that chronic degenerative pathologies, including IBD, share comparable disease mechanisms at the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 402 publications
(420 reference statements)
0
23
0
1
Order By: Relevance
“…Patients with colon cancer received treatment with resveratrol, and correlative laboratory studies examined its effects directly on colon cancer and normal colonic mucosa. Resveratrol may stop the growth of tumor cells by blocking some of the enzymes required for cell growth, and by inducing cell cycle arrest, apoptosis, inhibition of cell proliferation, stimulation of antiangiogenic responses and increased antioxidant and anti‐inflammatory activity (Talero et al., 2012). The activity of resveratrol shows great potential in the prevention and therapy of a wide variety of human diseases.…”
Section: Histone Modificators In Clinical Trialsmentioning
confidence: 99%
“…Patients with colon cancer received treatment with resveratrol, and correlative laboratory studies examined its effects directly on colon cancer and normal colonic mucosa. Resveratrol may stop the growth of tumor cells by blocking some of the enzymes required for cell growth, and by inducing cell cycle arrest, apoptosis, inhibition of cell proliferation, stimulation of antiangiogenic responses and increased antioxidant and anti‐inflammatory activity (Talero et al., 2012). The activity of resveratrol shows great potential in the prevention and therapy of a wide variety of human diseases.…”
Section: Histone Modificators In Clinical Trialsmentioning
confidence: 99%
“…Moreover, phytonutrients have received considerable attention because of their low cost and wide safety. Experimental evidence has established the potential colorectal cancer chemopreventive effects of plant-derived natural products [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, polyphenols have been reported to target cyclooxygenase-2 (COX-2) and scavenge ROS in tumor cells, indicating the antitumorigenic potentials of these compounds (23). In addition to the polyphenol compounds derived from phytonutrients, microalgal products have also exhibited chemopreventative activities in cancer cells (24). The chemical compound dibenziodolium chloride (DPI), which is a potent inhibitor of NOX, is thought to significantly suppress ROS levels, and Yamaura et al reported that inhibition of NOX activity by DPI arrests melanoma cells at the G2-M phase of the cell cycle (25).…”
Section: Introductionmentioning
confidence: 99%